2009
DOI: 10.1007/s10384-008-0604-0
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the Humphrey Matrix 24-2 test in the diagnosis of preperimetric glaucoma

Abstract: FDT Matrix seems to be a valuable clinical tool in the detection of preperimetric glaucoma. Among the parameters of the FDT Matrix, PDP analysis by modified Anderson criteria may provide a reliable cutoff criterion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…Multiple studies have also investigated the diagnostic capability for PPG using structural measurements with methods such as OCT (AUC = 0.527 to 0.938) 38–40 , HRT (AUC = 0.740 to 0.914) 39, 40 , and GDx (AUC = 0.688 to 0.894) 39 . Although it is difficult to make a direct statistical comparison between the AUC results of the current study and those of previous studies because of differences in sample size and characteristics, we report an AUC for PPG of 0.733 using Pulsar, similar to the results of previous studies on specific functional measurements 20, 31, 3537 . Although the AUC from Pulsar did not differ from other devices in the current study, the AUCs from specific functional measurements were slightly lower than those that have been reported by previous studies.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Multiple studies have also investigated the diagnostic capability for PPG using structural measurements with methods such as OCT (AUC = 0.527 to 0.938) 38–40 , HRT (AUC = 0.740 to 0.914) 39, 40 , and GDx (AUC = 0.688 to 0.894) 39 . Although it is difficult to make a direct statistical comparison between the AUC results of the current study and those of previous studies because of differences in sample size and characteristics, we report an AUC for PPG of 0.733 using Pulsar, similar to the results of previous studies on specific functional measurements 20, 31, 3537 . Although the AUC from Pulsar did not differ from other devices in the current study, the AUCs from specific functional measurements were slightly lower than those that have been reported by previous studies.…”
Section: Discussionsupporting
confidence: 85%
“…To date, many studies have reported on the diagnostic capability for PPG using specific functional measurements with methods such as FDT (AUC = 0.666 to 0.802) 20, 3537 , Flicker (AUC = 0.800) 20 , SWAP (AUC = 0.660 to 0.704) 20, 37 , and Pulsar (AUC = 0.733) 31 . Multiple studies have also investigated the diagnostic capability for PPG using structural measurements with methods such as OCT (AUC = 0.527 to 0.938) 38–40 , HRT (AUC = 0.740 to 0.914) 39, 40 , and GDx (AUC = 0.688 to 0.894) 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts have been made to discriminate PPG from healthy eyes by using various devices and special forms of perimetry, in a cross-sectional manner. Choi et al 17 have used MD and PSD of the Humphrey Matrix 24-2 test and obtained an AROC of 61.9% and 76.7% for each index, respectively; in their study PPG was diagnosed by using a combination of red-free fundus photography, Stratus optical coherence tomography (OCT), and stereophotography. 17 Leeprechanon et al 16 have used FDT and SWAP and reported AROCs of 62% (FDT MD), 67% (FDT PSD), 74% (SWAP MD), and 53% (SWAP MD), in which PPG was defined by abnormal findings with either OCT or Heidelberg retina tomograph (HRT).…”
Section: Discussionmentioning
confidence: 99%
“…1 In fact, it is now possible to detect early glaucomatous structural changes before the deterioration of patients' VFs becomes measurable, owing to the development of imaging devices, such as optical coherence tomography [2][3][4][5][6][7][8] and scanning laser polarimetry. 8,9 Furthermore, several studies have suggested that some forms of perimetry, such as frequency-doubling perimetry (FDT), [10][11][12][13][14][15][16] Humphrey Matrix 24-2 test, 17 short-wavelength automated perimetry (SWAP), 10,16,[18][19][20] and Heidelberg edge perimetry 21 may detect glaucomatous VF changes earlier than conventional standard automated perimetry (SAP).…”
mentioning
confidence: 99%
See 1 more Smart Citation